Confusing the grid: spatiotemporalities, queer imaginaries, and movement - Talburt, Susan; Matus, Claudia (Gender, place and culture : a journal of feminist geography, 2014)
Mediating between queer theory's privileging of time as actor and geographic emphases on material spaces and identities, this article engages feminist geographies and the work of Deleuze and Guattari to understand the implications of time and space as imagined, or actors' spatiotemporal imaginaries. We draw on Massumi's metaphor of the 'grid,' which sediments ways of seeing self and other and logics for action and interaction. The grid incites imaginaries of time as active and space as passive, which evoke past, present, and future, offering coordinates for locating identities. Focusing on spatiotemporality, we conduct a discourse analysis of interviews with two Chilean lesbian-feminist activists, focusing on (1) overtly spatial and temporal dimensions (nation, region, history), (2) the constitution of lesbian space and identity (identity, visibility, consciousness, and community), and (3) oppositional entities that stabilize lesbian identity and space (men, gay men, feminists, universities, and queer). We demonstrate how the activists' imagining of Chile as a space with a linear history with a fixed past and present directs their actions to a particular future of pre-given positions. Nonetheless, we point to moments of disidentificatory movement that returns analytic attention to process, creation, and the open potentiality of movement. The politics of spatiotemporal imaginaries offers activists, geographers, and queer theorists ways of narrating sexualized subjects and politics that are not repetitive of identitarian debates, history as necessary sequence, or spaces as material.